Epidemiological characteristics of hospitalized injury patients in a tertiary hospital of Guangxi Zhuang Autonomous Region, China: a retrospective single-center observational study - Chunxiu Yang; Jun Liang; Qingjiao Nong (BMC Public Health, 2026)
Abstract Background Injury is a substantial public health issue that ranks among the primary causes of mortality and disability globally. This study aimed to analyze the epidemiological characteristics and types of injury among hospitalized patients through a single-center hospital-based retrospective study conducted in Guangxi Zhuang Autonomous Region in China. Methods A total of 15,869 hospitalized injury patient records were retrieved from the Hospital Information System (HIS) of the People’s Hospital of Guangxi Zhuang Autonomous Region from 2018 to 2024. Results Among the 15,869 hospitalized injury patients, 9,828 were male (61.93%) and 6,041 were female (38.07%). Most injuries occurred among individuals aged 30–69 years (57.37%). The top three external causes of injury were falls (41.84%), exposure to inanimate mechanical forces (21.96%), and transport accidents (18.06%). Overall, head injuries were the most common type of injury (20.20%), and were associated with significantly increased odds of in-hospital death. For length of stay, the long durations were observed for certain early complications of trauma (IRR: 1.65; 95% CI: 1.41, 1.92), injuries involving multiple body regions (IRR: 1.63; 95% CI: 1.47, 1.81), and burns and corrosions (IRR: 1.47; 95% CI: 1.22, 1.78). Regarding hospitalization cost, the high expenses were incurred for other and unspecified effects of external causes (ER: 1.59; 95% CI: 1.25, 2.01), injuries involving multiple body regions (ER: 1.35; 95% CI: 1.18, 1.55), and injuries to the neck (ER: 1.21; 95% CI: 1.09, 1.34). Conclusion This study clarifies the epidemiological characteristics of hospitalized injury patients in a tertiary hospital of Guangxi Zhuang Autonomous Region. Falls are the leading external cause of injury, and head injuries are ranked as the primary cause of injury-related deaths.